The Migrant as the Protagonist of the 20th Century: A Comparative Analysis of Four Contemporary Authors (KULT_online, 2010)
In Migration and Literature Søren Frank argues against a restriction of the concept ‘migration’ to authorial-biographical approaches to literature, and for the development of ‘migration literature’ in opposition to the former ‘migrant literature’. He analyses four contemporary novelists — Grass, Kundera, Rushdie and Kjærstad — and shows how a wider conceptualisation of migration helps to reflect upon its thematic and formal roles in his readings of the novels. In comparing four authors from different countries and with different personal experiences of migration, Frank offers a wide-ranging insight into the pervasive influence of the social phenomenon of migration on the aesthetics of literature.